Subyearling Chinook salmon diets in Lower Columbia River estuarine habitats. - Kerry Accola; Jeff Cordell; Bob Oxborrow; Jason D Toft; Alyssa Suzumura; Jeffrey Grote (PLoS ONE)
The Lower Columbia River and Estuary is critical rearing habitat for juvenile Pacific salmon. Extending from the river mouth to Bonneville Dam 235 river kilometers upstream, the Estuary has been altered by dams, dikes, and habitat loss due to deforestation and wetland removal. Since 2008, five sites have been monitored to identify the long-term status and trends in Lower Columbia River and Estuary juvenile salmon rearing habitat. Here, we address predominantly natural origin juvenile Chinook Oncorhynchus tshawytscha diets and identify spatial and temporal trends in prey consumption, stomach fullness, energy consumption, and the metabolic costs associated with fish size and water temperatures. Juvenile Chinook diets consisted mainly of corophiid amphipods, chironomid dipterans, and cladocerans, with other insects filling in most of the remainder of their diets. Juvenile Chinook salmon diets were stable over time, and stomach fullness and caloric intake was comparable among the sites where most salmon were collected. Juvenile Chinook salmon were frequently in water temperatures above fitness thresholds and higher water temperatures and metabolic rates will require increased foraging as water temperatures rise. Reduced growth, earlier migration, and mismatches between prey production and foraging are near term possibilities. Juvenile salmon rearing resiliency in the estuary can be aided by maintaining sufficient river discharge levels for salmon, and by restoring habitat and habitat connectivity to the mainstem channel.